Methane-Rich Saline Counteracts Cholestasis-Induced Liver Damage via Regulating the TLR4/NF-κB/NLRP3 Inflammasome Pathway. (18th November 2019) - Li, Zeyu; Chen, Dongdong; Jia, Yifan; Feng, Yang; Wang, Cong; Tong, Yingmu; Cui, Ruixia; Qu, Kai; Liu, Chang; Zhang, Jingyao
Abstract : Cholestatic liver injury, due to obstruction of the biliary tract or genetic defects, is often accompanied by progressive inflammation and liver fibrosis. Methane-rich saline (MRS) has anti-inflammatory properties. However, whether MRS can provide protective effect in cholestatic liver injury is still unclear. In this study, Sprague-Dawley rats received bile duct ligation (BDL) to generate a cholestatic model followed by MRS treatment (10 mL/kg, ip treatment) every 12 h after the operation to explore the potential protective mechanism of MRS in cholestatic liver injury. We found that MRS effectively improved liver function, alleviated liver pathological damage, and localized infiltration of inflammatory cells. MRS treatment decreased the expression of hepatic fibrosis-associated proteins to alleviate liver fibrosis. Furthermore, MRS treatment suppressed the TLR4/NF- κ B pathway and further reduced the levels of proinflammatory factors. Downregulation of NF- κ B subsequently reduced the NLRP3 expression to inhibit pyroptosis. Our data indicated that methane treatment prevented cholestatic liver injury via anti-inflammatory properties that involved the TLR4/NF- κ B/NLRP3 signaling pathway.